Effectiveness of the Existence of Isimu Type a Terminal in the District of Gorontalo - Midun M Mahmud; Trisusanti Lamangida; Muh. Firyal Akbar (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This study aims to obtain information about the Effectiveness of Terminal Type A. Isimu in Gorontalo District, the research method uses qualitative type. Data collection techniques were carried out through interviews with a number of informants and observations and recording secondary data related to the research problem. The results of the study concluded that the achievement of the objectives showed that the existence of the Isimu Type A Terminal had not been effectively seen from the human resources owned and the infrastructure owned by the terminal was incomplete and not maintained. Whereas the other factor is the low awareness of the community in utilizing the terminal. So that the achievement of objectives has not been effective. While the Integration shows that communication between users and related parties is less than the maximum, it needs to be improved through socialization to increase understanding of service users. The Adaptation Indicator shows the benchmarks of the procurement and workforce filling process in supporting employee performance is not yet effective, seen from the lack of personnel and the lack of quality resources to support the effectiveness of the Isimu type A terminal.